Structured Waters Mediate Small Molecule Binding to G-Quadruplex Nucleic Acids - Stephen Neidle (MDPI AG, 2021)
The role of G-quadruplexes in human cancers is increasingly well-defined. Accordingly, G-quadruplexes can be suitable drug targets and many small molecules have been identified to date as G-quadruplex binders, some using computer-based design methods and co-crystal structures. The role of bound water molecules in the crystal structures of G-quadruplex-small molecule complexes has been analyzed in this study, focusing on the water arrangements in several G-quadruplex ligand complexes. One is the complex between the tetrasubstituted naphthalene diimide compound MM41 and a human intramolecular telomeric DNA G-quadruplex, and the others are in substituted acridine bimolecular G-quadruplex complexes. Bridging water molecules form most of the hydrogen-bond contacts between ligands and DNA in the parallel G-quadruplex structures examined here. Clusters of structured water molecules play essential roles in mediating between ligand side chain groups/chromophore core and G-quadruplex. These clusters tend to be conserved between complex and native G-quadruplex structures, suggesting that they more generally serve as platforms for ligand binding, and should be taken into account in docking and in silico studies.